2016
DOI: 10.1016/j.exger.2016.05.003
|View full text |Cite
|
Sign up to set email alerts
|

Dietary composition affects the development of cognitive deficits in WT and Tg AD model mice

Abstract: Clinical and epidemiological evidence suggests that lifestyle factors, including nutrition, may influence the chances of developing of Alzheimer’s disease (AD), and also likely affect the aging process. Whereas it is clear that high-fat diets are increasing both body weight and the risk of developing Alzheimer’s disease, to date, there have been very few studies comparing diets high with different sources of calories (i.e., high fat versus high protein versus high carbohydrates) to determine whether dietary co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 68 publications
1
5
0
Order By: Relevance
“…also on midlife intake). Our results point to reduction of fat intake in midlife and are in agreement with studies of Luchsinger et al [27], Laitinen et al [26] and with studies on rodents reported by Kadish et al [28] and Raider et al[29]. We propose only a modest shift in the consumption of fat, from the historical one, which we believe can reduce the AD susceptibility of a population, including also apolipoprotein E epsilon 4 allele carriers.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…also on midlife intake). Our results point to reduction of fat intake in midlife and are in agreement with studies of Luchsinger et al [27], Laitinen et al [26] and with studies on rodents reported by Kadish et al [28] and Raider et al[29]. We propose only a modest shift in the consumption of fat, from the historical one, which we believe can reduce the AD susceptibility of a population, including also apolipoprotein E epsilon 4 allele carriers.…”
Section: Discussionsupporting
confidence: 93%
“…All the confounding factors mentioned in our previous paper [6 and references therein] tend to reciprocally reduce their influence and we observe reasonable prediction as to the ratio and amounts of macronutrients. Our predictions are rather evolutionary than revolutionary and therefore seem to be safe to introduce to the society nutritional behaviors [28]. …”
Section: Discussionmentioning
confidence: 99%
“…A recent study demonstrated that a large increase in only one macronutrient, while keeping the other two at low percentages, exacerbates cognitive decline in a mouse model of Alzheimer’s disease (AD). 20 Similar studies have concluded that each macronutrient plays a critical role in brain health, but it is not known what ratios of macronutrients may be optimal for memory and cognition. However, such “one-nutrient-at-a-time” manipulations do not consider the interactive effects of single nutrient manipulations on balance with respect to other dietary components.…”
Section: Nutritional Interventions In Aging Researchmentioning
confidence: 99%
“…There is now ample evidence that diabetes and obesity-related metabolic dysfunction can accelerate the progression of other age-related diseases and pathologies in both mouse models of disease as well as normally aging mice (Butterfield et al, 2014;Farr et al, 2008;Morrison et al, 2010). For example, several reports have shown high fat diets, or insulin resistance, can accelerate learning and memory loss as well as neurodegeneration in different mouse models of AD (Kadish et al, 2016;Knight et al, 2014;Maesako et al, 2015;Morrison et al, 2010;Petrov et al, 2015). It is thus possible that obesity-related insulin resistance may be accelerating the aging progression (Salmon, 2016), and mitochondria and oxidative stress may play important role in this process.…”
Section: Mitochondria Mitochondrial Associated Membranes Ros and DImentioning
confidence: 99%